Nb-doped LiBH4 (010) surface for hydrogen desorption: First-principles calculations. (25th May 2015) - Yu, Suye; Ju, Xin; Wan, Chubin; Li, Shina
Abstract: Structural, electronic and energetics properties of Nb-doped LiBH4 (010) surface have been studied based on the first-principles density functional theory calculations. Three kinds of local structures are found during the dehydrogenation reaction of LiBH4, the most two favorable hydrogen desorption pathways are found to lead to NbH2 -BH2 -(BH4 )3 complex when the Nb occupies the top site of single B atom and lead to NbH2 -(BH3 )2 complex when the Nb occupies the bridge site of two adjacent B atoms. The formation of NbH2 and BH2 units in the NbH2 -BH2 -(BH4 )3 complex as well as the catalytic effect of Nb on the structures of surrounding (BH4 ) − units due to the orbital overlaps between Nb and inner B-H bonds in the complex. For the NbH2 -(BH3 )2 complex, NbH2 and NbB2 phases may be formed in sequence accompanied by the dehydrogenation reaction. The results are in good agreement with the report of Wang, KK et al. experimentally. The calculated average hydrogen desorption energies of Nb-doped LiBH4 (010) surface are smaller than the pure LiBH4 (010) surface about 1.7 eV and 1.5 eV, respectively. These properties reveal that the import of Nb has great effect on reducing the bond strength of B-H. Highlights: NbH2 -BH2 -(BH4 )3 and NbH2 -(BH3 )2 complexes are found during the dehydrogenation reaction of Nb-doped LiBH4 . NbH2 and NbB2 phases may be formed in sequence accompanied by the dehydrogenation reaction. The calculated average hydrogen desorption energies of Nb-doped LiBH4 are much smaller than the pure.